Glutamate oxaloacetate transaminase enables anaplerotic refilling of TCA cycle intermediates in stroke-affected brain - Rink, Cameron (FASEB J, 2017)
Ischemic stroke results in excessive release of glutamate, which contributes to neuronal cell death. Here, we test the hypothesis that otherwise neurotoxic glutamate can be productively metabolized by glutamate oxaloacetate transaminase (GOT) to maintain cellular energetics and protect the brain from ischemic stroke injury. The GOT-dependent metabolism of glutamate was studied in primary neural cells and in stroke-affected C57-BL6 mice using magnetic resonance spectroscopy and GC-MS. Extracellular Glu sustained cell viability under hypoglycemic conditions and increased GOT-mediated metabolism in vitro. Correction of stroke-induced hypoxia using supplemental oxygen in vivo lowered Glu levels as measured by (1)H magnetic resonance spectroscopy. GOT knockdown abrogated this effect and caused ATP loss in the stroke-affected brain. GOT overexpression increased anaplerotic refilling of tricarboxylic acid cycle intermediates in mouse brain during ischemic stroke. Furthermore, GOT overexpression not only reduced ischemic stroke lesion volume but also attenuated neurodegeneration and improved poststroke sensorimotor function. Taken together, our results support a new paradigm that GOT enables metabolism of otherwise neurotoxic extracellular Glu through a truncated tricarboxylic acid cycle under hypoglycemic conditions.—Rink, C., Gnyawali, S., Stewart, R., Teplitsky, S., Harris, H., Roy, S., Sen, C. K., Khanna, S. Glutamate oxaloacetate transaminase enables anaplerotic refilling of TCA cycle intermediates in stroke-affected brain.